Efektivitas kombinasi Pistia stratiotes L. dan Salvinia molesta Mitchell dalam fitoremediasi air asam tambang batubara - Putri, Deviana; Juswardi, Juswardi (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
Open pit mining is a mining system that is commonly applied to coal extraction activities. Environmental problems in coal mining activities are generally related to acid mine drainage (AMD). Efforts to overcome the impact of AMD can be done by phytoremediation in constructed wetlands (CW). Plants that have the potential for AMD phytoremediation include Pistia stratiotes L (water lettuce) and Salvinia molesta Mitchell (giant Salvinia) , so it is necessary to conduct research on the effectiveness of the combination of P. stratiotes and S. molesta to be developed on CW vegetation. The experimental design used was a completely randomized design (CRD), with 3 treatments using P. Stratiotes, S. Molesta, Combination of P. stratiotes and S. molesta each 9 replications. The results showed the effectiveness of phytoremediation using plant vegetation of P. stratiotes and S. molesta in increasing pH by 40.04% and reducing sulfate levels by 41.72%. The effectiveness of the combination of P. stratiotes and S. molesta in reducing levels of Mn and Fe were 101.36% and 93.49%, respectively. The decrease in TSS levels is better done by the combination of P. stratiotes and S. Molesta vegetation compared to P. stratiotes or S. Molesta vegetation alone, but the better growth rate occurred in S. molesta vegetation only.